Efficacy of 0.01% Atropine for Myopia Progression in Children Aged 5 Years to 16 Years - Yadav, Navin; Malik, Anu; Dr. R.C. Gupta,; Gupta, Alka; Singh, Lokesh Kumar; Jaishree Dwivedi, (Nepalese Journal of Ophthalmology, 2026)
Introduction: Myopia is an increasingly prevalent global public health concern, particularly among children, with potential long-term visual complications. Low-dose atropine has emerged as promising pharmacological intervention for controlling myopia progression.Objective: To evaluate the efficacy and safety of 0.01% atropine eye drops in controlling myopia progression in children over one year.Methodology: A placebo-controlled, interventional study was conducted for one year in ophthalmology department of a tertiary care centre. A total of 189 eyes (95 participants) were included in treatment group and 150 eyes (75 participants) in control group. Baseline and follow-up assessments at four, eight, and 12 months included axial length, spherical equivalent, distance uncorrected visual acuity, amplitude of accommodation, intraocular pressure, pupil diameter, and fundus examination. Statistical analysis was performed using Epi Info software, and a p-value